Financial Analysis of the Video Assisted Thoracoscopic Surgery versus Open Thoracotomy in Management of Pediatric Parapneumonic Empyema: Financial Analysis of the Video Assisted Thoracoscopic Surgery - Mohajerzadeh, Leily; Harirforoosh, Iman; Ebrahimisaraj, Gholamreza; Atqiaee, Khashayar (Iranian Journal of Pediatric Surgery, 2022)
Introduction: In this article we will evaluate the cost of these two techniques for management of parapneumonic empyema. Aim of this study is comparison of the Cost- benefit of the less invasive Thoracoscopic Approach (VATS) versus Open Thoracotomy in pediatric patients with. Materials and Methods: A prospective study was done on 42 patients referred to Department of Pediatric Surgery, between 2015 and 2017. Patients were divided randomly into two groups of open thoracotomy(group I) and VATS (group II). Both groups were similar by terms of age (mean 6 years), number of patients (22/20), sex (1.1 male/female)and comorbidities. Routine preliminary workups were ordered for all patients. Patients were followed up for a course of 90 days to evaluate the results of the treatment and the incidence of complications and death. To calculate the cost of each method we take into account the defined parameters: Results: The mean operative time (60versus45 minutes), the average of drainage time (7 versus 5 days), average length of hospital stay (23 versus 13 days) (p=0.007), and duration of pain–relief medications (10 versus 5 days) (p=0.004), were longer in group I. 27.3% of group I had surgical wound infection but no such case was seen in group II (p = .003). Redo thoracotomy due to lack of clinical improvement in group I and II, was observed in 9.1% versus 20%, respectively. Death due to pulmonary complications during the first 30 days after the surgery was seen in one case in the group I. The mean cost for VATS is about 1045.9$ versus 976,32$ for open thoracotomy technique. Conclusion: Apart from other benefits of VATS technique such as less postoperative hospital stay, that has been shown in the previous article published by our team, now we can highly recommend this technique because of the lack of any significant cost difference between the VATS and open thoracotomy technique.